(612) General Purpose Systems Simulator (GPSS) محاكي أنظمة الأغراض العامة (GPSS) - Alwalid El Sahfei. (معهد التخطيط القومى، المعهد العربى للتخطيط بالكويت, 2024)
The General Purpose Systems Simulator (GPSS) is a language used to define basic actions typical of discrete systems in general. In GPSS, a physical system can be sufficiently described for simulation through block diagrams familiar to many engineers and each transaction can represent various entities like a message in a communication network, a pulse in an electrical circuit, a work-order in a shop, or a shopper entering a supermarket.